Isolation and Characterization of Chemical Constituents from the Petals of Nelumbo nucifera - Xu, Shuangshuang; Duan, Wenjuan; Fang, Lei; Sun, Yu; Dong, Hongjing; Wang, Xiao (Asian Journal of Chemistry, 2012)
In the present study, eight compounds were isolated and characterized from ethanolic extract of the petals of Nelumbo nucifera. These compounds were elucidated as myricetin-3-O-b-D-glucopyranoside (I), quercetin-3-O-b-D-glucuronide (II), astragalin (III), quercetin (IV), 3,4-dihydroxybenzoic (V), kaempeforol (VI), p-hydroxybenzoic acid (VII) and b-sitosterol (VIII). Among these compounds, compounds I, II, IV, V, VI, VII and VIII were isolated from the petals of Nelumbo nucifera for the first time and compounds I and V were first reported from the genus of Nelumbo.